2017
DOI: 10.1182/blood-2016-12-754796
|View full text |Cite
|
Sign up to set email alerts
|

Genetic abnormalities in myelodysplasia and secondary acute myeloid leukemia: impact on outcome of stem cell transplantation

Abstract: Key Points• TP53 and RAS-pathway mutations predict very poor survival, when seen with CK and MDS/MPNs, respectively. • For patients with mutated TP53 or CK alone, long-term survival could be obtained with stem cell transplantation.Genetic alterations, including mutations and copy-number alterations, are central to the pathogenesis of myelodysplastic syndromes and related diseases (myelodysplasia), but their roles in allogeneic stem cell transplantation have not fully been studied in a large cohort of patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
230
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 293 publications
(244 citation statements)
references
References 55 publications
12
230
0
2
Order By: Relevance
“…Recent studies showed that mutations in TP53 and Ras-pathway were associated with relapse and surivival after HCT. 30,31 These mutations might also affect the relapse incidences after HCT. Thus, the proportion of blast and molecular profiles need to be included for analyzing the propensity score matching in the future study.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that mutations in TP53 and Ras-pathway were associated with relapse and surivival after HCT. 30,31 These mutations might also affect the relapse incidences after HCT. Thus, the proportion of blast and molecular profiles need to be included for analyzing the propensity score matching in the future study.…”
Section: Discussionmentioning
confidence: 99%
“…Allele specific copy-number profiles were generated from NGS data using CNACS 9 . CBA data were available for 2,931 (88%) patients.…”
Section: Characterization Of Genome Wide Allelic Imbalances In Mdsmentioning
confidence: 99%
“…We assessed chromosomal alterations based on NGS sequencing data using CNACS 9 . CNACS enables the detection of arm level and focal copy-numbers changes as well as regions of cnLOH.…”
Section: Copy Number Analysismentioning
confidence: 99%
“…Besides known risk factors such as remission state or karyotype knowledge about specific somatic mutations will also be incorporated into such stratification algorithms. Potential candidates for this seem to be TP53 mutations, as several analyses indicated a dismal prognosis for MDS patients after allo-SCT [65][66][67][68]. The goal is to identify a patient population with an extraordinary high relapse risk for further studies to test innovative prophylactic strategies after transplant.…”
Section: Prophylactic or Pre-emptive Therapy With Hma?mentioning
confidence: 99%